The prognostic importance of platelet indices in patients with Crimean-Congo Hemorrhagic Fever. (4th October 2017) - Aksoy, Firdevs; Yilmaz, Gürdal; Kaya, Selcuk; Karahan, Süleyman Caner; Koksal, Iftihar
Abstract: Background: Platelet count is an important tool for the diagnosis and prognosis of Crimean-Congo Hemorrhagic Fever (CCHF). The platelet indices plateletcrit, mean platelet volume (MPV) and platelet distribution width (PDW) are parameters obtained as part of the automated complete blood count. These parameters are of prognostic importance in several diseases. The aim of this study was to evaluate the platelet count and its relations with platelet indices in CCHF patients. Methods: One hundred and forty-nine patients with confirmed CCHF were included in the study. Patients were divided into two groups (severe cases, patients who exhibited hemorrhage during their hospital stay, and mild/moderate cases with no hemorrhage during hospital stay). The demographic characteristics and laboratory test results of all patients were compared. P < 0.05 was regarded as statistically significant. Results: Hemorrhaging was observed in 38.3% of patients during hospitalization. Platelet count, PCT and PDW values (respectively) on the first day of hospitalization were 43.3 ± 29.3, 0.06 ± 0.07%, and 17.4 ± 1.5% in the severe cases and 64.5 ± 35.4, 0.08 ± 0.03%, and 16.8 ± 1.5% in the mild/moderate cases, respectively ( P < 0.05). The difference between MPV values was not statistically significant. At cutoff values at ROC analysis, platelet count (≤53000) and PCT(≤0.06) exhibited 73.7% and 71.9% sensitivity, respectively, and predicted a hemorrhagic disease course with a 80.9% negative predictive value. Seven of the severe patients died ( P = 0.001). At cutoff values, platelet count (>31000) and PCT (>0.03) predicted patient survival with 100% specificity and 100% positive predictive value. Conclusion: Our study shows that platelet count, PCT and PDW are parameters that may be used to determine disease severity. The platelet index, and particularly PCT, may be at least as useful as platelet count in helping clinicians identify severe cases. Disclosures: All authors: No reported disclosures.